Confucianism: measurement and association with workforce performance. Issue 2 (20th March 2018) - Viengkham, Doris; Baumann, Chris; Winzar, Hume
Abstract : Purpose: This paper reconsiders the approaches to measuring Confucian values, and tests their association with workforce performance. The purpose of this paper is to examine how such values and performances are prioritized across three East Asian societies, but more importantly, identifies how variations across societies might result from the way in which Confucianism has been transformed/appropriated differently across history. Design/methodology/approach: A Best-Worst experimental design is used to measure three aspects of Confucianism (relational, pedagogical, and transformative), and three aspects of workforce performance (mindset, organization, and process) to capture the trade-offs by respondents from three East Asian societies: China ( n =274), Taiwan ( n =264), and South Korea ( n =254). The study employs analysis of variance with post-hoc tests to examine differences between societies. A hierarchical cluster analysis using Ward's method is utilized to identify clusters based on similarities within the data. And last, multiple regression analysis is applied to determine the explanatory power of Confucian values on workforce performance. Findings: Findings confirm the prioritization of three aspects of Confucianism (relational, pedagogical, and transformative) to differ between Mainland Chinese, Taiwan Chinese, and Korean respondents – producing five distinct clusters based on similarities across three societies. Overall, between 7 and 27 percent of the variance in workforce performance could be explained by the Confucian values included in this study. Originality/value: This study highlights the "different shades of Confucianism" across East Asian societies, which we coin as Confucian Origin, Preservation, and Pragmatism, and demonstrates the need to take a multifaceted perspective in the measurement of Confucian culture. The study provides empirical support for the link between Confucianism and performance at the micro-level, as originally proposed by Baumann and Winzar (2017), and identifies specific antecedents of behavior for research moving forward.